(untitled) (Journal of Nepal Geological Society, 2001)
Palynological study of a series of slimes obtained from a 284-m-long drill well in the Kathmandu Basin revealed palaeoclimatic records and deposition al environmental changes in the Kathmandu Valley during the last 2.5 myr. The slimes consist of fluvio-deltaic and lacustrine sediments comprising 218 m long muddy beds and 66.3 m of sandy beds. As a result of palynological study on the 189 pieces of slime, a total 43 types of fossil pollen and spores were identified. They comprise arboreal pollen of one family and 20 genera, non-arboreal pollen of 10 families and 10 genera and spores. In the pollen diagram, Quercus and Cyclobalanopsis are predominant, with frequencies exceeding 70%. Pinus, Alnus and Gramineae are the next dominant taxa. Three fossil pollen zones, which reflect major climatic change, were discriminated: Zone I indicates a cool climate from ca. 2.5 to 2.1 Ma; Zone II shows a warm and relatively dry climate without remarkable fluctuation from ca. 2.1 to 1.0 Ma; and Zone III is characterized by seven cycles of warm-and-wet and cold-and-dry climate from 1.0 Ma to present, which reflect the repetition of glacial and interglacial periods. The last cold maximum at 11 m depth seems to correspond to the last glacial age around 20 kyr B.P. The sedimentation rate of the drill-well was estimated from an approximate age-depth plot based on approximate ages inferred by comparison between the palaeoclimatic curve drawn by pollen analysis and δ18O curve obtained from planktonic foraminifers of deep-sea sediments in the Indian Ocean. Consequently, the average sedimentation rate of the uppermost part from 115 m to 11 m in depth is estimated at 104 mm/kyr.